2021
DOI: 10.1108/hff-03-2021-0161
|View full text |Cite
|
Sign up to set email alerts
|

Linear stability analysis of non-Newtonian blood flow with magnetic nanoparticles: application to controlled drug delivery

Abstract: Purpose For this purpose, a linear stability analysis based on the Navier–Stokes and Maxwell equations is made leading to an eigenvalue differential equation of the modified Orr–Sommerfeld type which is solved numerically by the spectral collocation method based on Chebyshev polynomials. Unlike previous studies, blood is considered as a non-Newtonian fluid. The effects of various parameters such as volume fraction of nanoparticles, Casson parameter, Darcy number, Hartmann number on flow stability were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(77 reference statements)
0
2
0
Order By: Relevance
“…Blood was modelled with uniform density, r = 1060 kg/m 3 , and laminar flow conditions were assumed due to the low Reynolds numbersless than 1300 (Yamamoto et al, 2004) in the renal vasculature. Numerical studies have shown that factors including the non-Newtonian properties of blood and body accelerations can affect solute dispersion in blood flow (Saadun et al, 2021); non-Newtonian properties have also been shown to be essential when modelling targeted delivery of therapeutic agents (Tiam Kapen et al, 2022). Nonetheless, a constant viscosity of m = 0.00345 Pa•s, based on blood's lowest viscosity limit, was ascribed to the blood for three main reasons: it yields more exaggerated flow disturbances than non-Newtonian blood rheological models (Vijayaratnam et al, 2015); the wall shear stress thresholds used in the present study were originally obtained (Chen et al, 2015;LaDisa et al, 2004), and; the choice of blood rheological model has negligible impact on the drug transport behaviour in the context of stented arteries (Vijayaratnam et al, 2015(Vijayaratnam et al, , 2019.…”
Section: Hff 3212mentioning
confidence: 99%
“…Blood was modelled with uniform density, r = 1060 kg/m 3 , and laminar flow conditions were assumed due to the low Reynolds numbersless than 1300 (Yamamoto et al, 2004) in the renal vasculature. Numerical studies have shown that factors including the non-Newtonian properties of blood and body accelerations can affect solute dispersion in blood flow (Saadun et al, 2021); non-Newtonian properties have also been shown to be essential when modelling targeted delivery of therapeutic agents (Tiam Kapen et al, 2022). Nonetheless, a constant viscosity of m = 0.00345 Pa•s, based on blood's lowest viscosity limit, was ascribed to the blood for three main reasons: it yields more exaggerated flow disturbances than non-Newtonian blood rheological models (Vijayaratnam et al, 2015); the wall shear stress thresholds used in the present study were originally obtained (Chen et al, 2015;LaDisa et al, 2004), and; the choice of blood rheological model has negligible impact on the drug transport behaviour in the context of stented arteries (Vijayaratnam et al, 2015(Vijayaratnam et al, , 2019.…”
Section: Hff 3212mentioning
confidence: 99%
“…Sutterby fluid acted as a base fluid that was non-Newtonian in nature. Tiam et al [8] analyzed the linear stability of blood flow consisting of magnetic nanoparticles and investigated the controlled drug delivery taking place in a porous artery in the presence of a magnetic field. Their study placed importance on controlling the mobility of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%